Students’ Responsibility Awareness: An Explanatory Sequential Mixed-Methods Study at a Junior High School - Rifka Putri Tasya; Rido Setiawan; Riza Adzkia; Shalza Amanda; Sri Dewi; Asni Asni (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2026)
This study examined students’ responsibility awareness at SMPN X, South Jakarta, from a developmental perspective. Previous studies have investigated adolescent responsibility, moral development, self-regulation, and character education; however, limited research has specifically examined responsibility awareness as a developmental task within the context of school guidance and counseling by integrating quantitative developmental assessment with qualitative exploration. Therefore, this study employed an explanatory sequential mixed-methods design. The quantitative phase involved 360 seventh- and eighth-grade students selected through total sampling using the Developmental Task Inventory (DTI), and the data were analyzed using the Developmental Task Analysis (DTA) software. The qualitative phase involved one school counselor and two homeroom teachers selected through purposive sampling, and the interview data were analyzed using coding and thematic analysis. The findings indicate that students’ responsibility awareness scores ranged from 3.39 to 3.81, placing most students between the Conformity and Self-Awareness developmental stages. Responsible behavior was generally evident in academic engagement and compliance with school regulations but remained largely influenced by external supervision. Teacher role modeling, a positive school climate, and supportive peer relationships facilitated the internalization of responsibility, whereas limited parental involvement and insufficient moral reasoning hindered its development. These findings highlight the importance of strengthening guidance and counseling services to promote moral internalization, self-regulation, and collaboration between schools and families in fostering autonomous responsibility.